Comparative Analysis of Treatment Modalities for Bell’s Palsy and Their Effectiveness - Ilias, Mohammad (IAHS Medical Journal, 2025)
Background: Bell's Palsy is an acute peripheral facial neuropathy characterized by sudden, unilateral facial paralysis. Various treatment modalities, including corticosteroids, antivirals, combination therapies, physiotherapy, and acupuncture, have been explored to enhance recovery and improve outcomes. This study aims to comparatively analyze the effectiveness of different treatment modalities for Bell's Palsy, focusing on facial nerve recovery, quality of life, pain levels, adverse effects and treatment adherence. Materials and methods: A prospective, randomized controlled trial involving 300 participants diagnosed with Bell's Palsy was conducted across multiple centers during the period from January to June 2024. Participants were randomly assigned to one of six treatment groups: corticosteroids, antivirals, combination therapy (Corticosteroids and antivirals) physiotherapy, acupuncture or control (Placebo or no treatment). Primary and secondary outcomes were assessed using the House-Brackmann facial nerve grading system, Facial Disability Index (FDI) and Visual Analog Scale (VAS) for pain at baseline, 1 month, 3 months and 6 months post-treatment. Adverse effects and treatment adherence were also recorded. Results: Combination therapy showed the most significant improvement in facial nerve recovery, with mean House- Brackmann grades improving from 3.1 at baseline to 1.1 at 6 months. The Combination group also reported the highest mean FDI score (78.5) and the lowest VAS pain score (1.9). The Corticosteroids group showed substantial improvements but to a lesser extent than the Combination group. Adverse effects were most common in the Corticosteroids and Combination groups, with insomnia and gastrointestinal issues being the most frequently reported. Treatment adherence was high across all groups, with the highest adherence in the Control group (95%). Conclusion: Combination therapy with corticosteroids and antivirals is the most effective treatment modality for Bell's Palsy, significantly improving facial nerve recovery, quality of life and pain outcomes. Despite some adverse effects, the overall benefits support the use of combination therapy as the standard approach in managing Bell's Palsy. Future research should focus on optimizing treatment protocols and exploring long-term outcomes to further substantiate these findings. IAHS Medical Journal Vol 7(2), December 2024; 47-51